Differences of compressive strength between calcium carbonate from blood clam shells and calcium hydroxide as a candidate for pulp capping material - Saraswati, Widya; Juniarti, Devi Eka; Lestari, Vita; Soetojo, Adioro; Kunarti, Sri; Cahyani, Febriastuti; Suardita, Ketut; Rahardia, Nabiela (Conservative Dentistry Journal, 2024)
Background: Pulp capping is one of the treatments for reversible pulpitis and aims to maintain pulp vitality. This treatment requires a material that can protect the pulp with good biocompatibility. The physical and mechanical properties, bio interactivity and bioactivity of pulp capping materials are very important for the formation of reparative dentin. Calcium hydroxide (Ca(OH)2) as the gold standard material in pulp capping treatment also has some disadvantages. Another alternative for pulp capping material is blood clam shell because it contains 98% calcium carbonate (CaCO3), which is a compound with a bone-like structure and can induce pulp cell differentiation. Objective: To investigate and explain the difference in compressive strength between CaCO3 from blood clam shells and Ca(OH)2 as a candidate pulp capping material. Methods: This research is a laboratory experimental study with post test only control group design method. Ca(OH)2 and CaCO3 samples were formed with a mixture of powder and aquadest with 4x6 mm sample size. The samples were dried at room temperature and the compressive strength was measured using a universal testing machine (UTM). Result: There is a significant difference in compressive strength between Ca(OH)2 and CaCO3 blood clam shells in the Mann-Whitney test results (p<0.05). Conclusion: The results of the compressive strength test between the mixture of Ca(OH)2 with aquadest in a ratio of 1:1 are greater than the mixture of CaCO3 blood clam shells with aquadest in a ratio of 3:1 so that pure CaCO3 blood clam shells with distilled water without other additives cannot be used as a candidate for capping pulp material.